Mediamorphosis of Radio Broadcasting on a Drive-in Concert Event during Pandemic Era - Vincent Atmadja; Alfred Pieter Menayang; Rustono Farady Marta; Yohanes Nugroho Widiyanto (Nyimak: Journal of Communication, 2021)
Radio listeners in Indonesia amounted to 11.1 million in 2019, which is the highest number in the last 4 (four) years. Radio is one of the broadcasting communication media that is still very effective for entertainment purposes, accurate information, news, advertising, and also educational purposes. Intensified by the existence of radio streaming applications, there has been the development of loyal listeners due to its easier access. The fact that  radio broadcasting media is still popular for advertising purposes, PT. Berlian Entertainment then decided to cooperate with Mahaka Radio Integra in marketing and conducting a drive-in concert event. This study aims to analyze the role of Mahaka Radio Integra Broadcasting in marketing and organizing a drive-in concert named after “Danamon New Life Experience”. The paradigm in this study is a constructivist paradigm with sociocultural traditions and qualitative approaches. The method used in compiling this study is Gamson and Modigliani’s Framing Analysis with research theory based on Marshall McLuhan’s Technological Determinism. From various news headlines displayed by online media such as Beritasatu, Kompas.com, JakartaPost, and Tribunews, it can be concluded that the drive-in concert event is the first event which applied health protocols while watching behind the wheel of the car, and enjoying the music. The convergence between online and offline media is one of the innovations for this drive-in concert itself, and this convergence is part of Mediamorphosis. Music lovers who miss watching musical concerts because of the pandemic can enjoy the concert by utilizing the online FM radio signal presented in their cars and can also see the live performance of the musicians behind their wheels.Keywords: Radio broadcasting role, drive-in concert event, convergence, framing analysis, technological determinism, mediamorphosis ABSTRAKJumlah pendengar radio di Indonesia mencapai 11,1 juta pada tahun 2019, yang merupakan jumlah tertinggi dalam 4 (empat) tahun terakhir. Radio merupakan salah satu media komunikasi penyiaran yang masih sangat efektif untuk tujuan hiburan, mendengarkan informasi akurat, berita, iklan dan juga tujuan pendidikan. Ditambah lagi dengan adanya aplikasi streaming radio yang memudahkan pendengar setia untuk terus mengikuti siarannya. Efektivitas periklanan dengan menggunakan media penyiaran radio dilihat oleh PT. Berlian Entertainment yang kemudian memutuskan untuk bekerjasama dengan Mahaka Radio Integra dalam memasarkan Event Drive-in concert yang akan diadakan. Penelitian ini bertujuan untuk menganalisis peran broadcasting Mahaka Radio Integra dalam memasarkan Event Drive-in concert yang diselenggarakan oleh PT. Berlian Entertainment dalam “Danamon New Life Experience”. Paradigma dalam penelitian ini adalah paradigma konstruktivis dengan tradisi sosiokultural dan pendekatan kualitatif. Metode yang digunakan dalam penelitian ini adalah Analisis Framing Gamson dan Modigliani dengan teori penelitian berdasarkan Technological Determinism Marshall McLuhan. Dari berbagai headline berita yang ditampilkan oleh media online seperti Beritasatu, Kompas.com, JakartaPost, dan Tribunews dapat disimpulkan bahwa pemberitaan yang diberikan mengenai acara konser drive-in ini merupakan acara pertama yang dilakukan Berlian Entertainment bersama Mahaka Radio Integra dengan menerapkan protokol kesehatan, menonton di belakang kemudi, dan suguhan musik. Konvergensi antara media daring dan luring menjadi salah satu inovasi bagi drive-in concert ini sendiri, dan hal ini menjadi salah satu bagian dari Mediamorfosis. Pecinta yang rindu menonton konser musik dapat menikmati konser tersebut dengan memanfaatkan sinyal radio FM secara daring yang dihadirkan di mobil masing-masing dan juga dapat melihat musisi yang bermain musik menggunakan sound system secara luring.Kata Kunci: Peran penyiaran radio, konvergensi event drive-in concert, analisis framing, technological determinism,mediamorfosis